Towards a European Energy Union : European energy strategy in international law / Volker Roeben, University of Dundee. - Roeben, Volker (Cambridge University Press, 2018)
The European Union is poised to establish a genuine European Energy Union with the new powers conferred on it by the Lisbon Treaty. Since 2014, it has been developing and implementing an energy strategy that responds to the three overarching priorities of climate change, political security, and economic competitiveness by 2030. The European Energy Union aims to provide secure, sustainable and affordable energy throughout the cycle of production, transport and consumption. This book outlines the legal regime underpinning this regulatory strategy, which integrates EU law with international law and with the law of the member states and affiliated states. It analyses and explains the increasing interaction between these legal orders in achieving the shared objective of transforming the European and global energy systems. This book will appeal to scholars and students of energy law and Policy at both European and international levels.